2020
DOI: 10.32526/ennrj.18.2.2020.19
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Flooding of Two Riparian Tree Species in the Lowland Tropical Forests of Thailand

Abstract: Responses of riparian woody species, especially in the tropical forests of Thailand, under flooding condition remain unknown. The effects of flooding on growth of the native species, Hydnocarpus anthelminthicus and Xanthophyllum lanceatum, which dominate in the lowland tropical forests in the East of Thailand, were observed during 16 weeks. The growth and morphological responses were determined in one-year-old seedlings, which stems were submerged at a level of 3 cm above the soil surface (flooded). They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Other studies have also shown physiological and anatomical adaptations to flooding in flood‐tolerant species (Lopez & Kursar, 2003; Ow et al., 2019; Silva et al., 2010). Overall, studies have shown that, as expected, flooding reduced root biomass (Pisicchio et al., 2010), root: shoot ratio (Moungsrimuangdee et al., 2020), root productivity (Lopez & Kursar, 2003; Silva et al., 2010) and rooting depth (Lopez & Kursar, 2003) from tropical trees (Figure 4).…”
Section: Resultssupporting
confidence: 59%
“…Other studies have also shown physiological and anatomical adaptations to flooding in flood‐tolerant species (Lopez & Kursar, 2003; Ow et al., 2019; Silva et al., 2010). Overall, studies have shown that, as expected, flooding reduced root biomass (Pisicchio et al., 2010), root: shoot ratio (Moungsrimuangdee et al., 2020), root productivity (Lopez & Kursar, 2003; Silva et al., 2010) and rooting depth (Lopez & Kursar, 2003) from tropical trees (Figure 4).…”
Section: Resultssupporting
confidence: 59%
“…O alagamento também induz alterações morfológicas de espécies de zonas úmidas, por exemplo, a formação de raízes adventícias e lenticelas hipertrofiadas (Moungsrimuangdee et al, 2020). No presente estudo, não foi verificado a presença de raízes adventícias e nem de lenticelas hipertrofiadas, poros usados para troca de gás.…”
Section: Resultsunclassified
“…No presente estudo, não foi verificado a presença de raízes adventícias e nem de lenticelas hipertrofiadas, poros usados para troca de gás. A falta dessas estruturas pode afetar tanto o crescimento quanto o desenvolvimento da raiz e parte aérea nas espécies lenhosas alagadas (Moungsrimuangdee et al, 2020). Alguns trabalhos reportam a importância das raízes adventícias para a recuperação da taxa fotossintética e para o crescimento em altura e diâmetro do caule em mudas inundadas (Mielke et al, 2005;Iwanaga & Yamamoto, 2008).…”
Section: Resultsunclassified
See 2 more Smart Citations